17β‐estradiol reduces SARS‐CoV‐2 infection in vitro. Issue 2 (19th January 2021) - Lemes, Robertha Mariana Rodrigues; Costa, Angelica Jardim; Bartolomeo, Cynthia Silva; Bassani, Taysa Bervian; Nishino, Michelle Sayuri; Pereira, Gustavo Jose da Silva; Smaili, Soraya Soubhi; Maciel, Rui Monteiro de Barros; Braconi, Carla Torres; da Cruz, Edgar Ferreira; Ramirez, Ana Lopez; Maricatto, Juliana Terzi; et al.
Abstract: The COVID‐19 has originated from Wuhan, China, in December 2019 and has been affecting the public health system, society, and economy in an unheard‐of manner. There is no specific treatment or vaccine available for COVID‐19. Previous data showed that men are more affected than women by COVID‐19, then we hypothesized whether sex hormones could be protecting the female organism against the infection. VERO E6 cells have been commonly used as in vitro model for SARS‐CoV‐2 infection. In our experimental approach, we have treated VERO E6 cells with 17β‐estradiol to evaluate the modulation of SARS‐CoV‐2 infection in this cell line. Here we demonstrated that estrogen protein receptors ERα, ERβ, and GPER1 are expressed by VERO E6 cells and could be used to study the effects of this steroid hormone. Previous and 24‐hours post‐infection, cells treated with 17β‐estradiol revealed a reduction in the viral load. Afterward, we found that SARS‐CoV‐2 infection per se results in ACE2 and TMPRSS2 increased gene expression in VERO E6‐cell, which could be generating a cycle of virus infection in host cells. The estrogen treatment reduces the levels of the TMPRSS2, which are involved with SARS‐CoV‐2 infectiveness capacity, and hence, reducing the pathogenicity/genesis. These data suggest that estrogen could be a potential therapeutic target promoting cell protection against SARS‐CoV‐2. This opens new possibilities for further studies on 17β‐estradiol in human cell lines infected by SARS‐CoV‐2 and at least in part, explain why men developed a more severe COVID‐19 compared to women. Abstract : The results show that 17β‐estradiol can reduce SARS‐CoV‐2 infection in vitro. Additionally, estrogen can reduce TMPRSS2 gene expression after SARS‐CoV‐2 infection, which is involved with coronavirus infectiveness capacity.